(untitled) (Bangladesh Journal of Medical Science, 2013)
Introduction: Maternal thyroid dysfunction during pregnancy has been associated with a number of adverse outcomes, like preterm birth, placental abruption, foetal death and impaired neurological development in the child. Simultaneously the presence of antibody to thyroid peroxidase results miscarriage, preterm birth and maternal post partum thyroid disease. Post partum thyroiditis is closely associated with the presence of antibodies to thyroid peroxidase (TPO). Indeed if a pregnant woman is positive for TPO antibodies early in pregnancy, her chances of developing post partum thyroiditis is 30-52%. Objective: To find out the level of TPO-Ab and thyroid status in first trimester of pregnancy. Method: The cross sectional study was designed in Department of Biochemistry, BSMMU, Dhaka. Following inclusion and exclusion criteria 200 sample was selected by purposive and convenient sampling. The study parameters were- thyroid peroxidase antibody (TPO-Ab); serum thyroid stimulating hormone (TSH); serum free thyroxin (FT4). Results: 43 (21.5%) pregnant women of first trimester was found to be TPO-Ab positive, among these 43 subjects 16 (8.0%) had raised TSH i.e. >2.5 mIU/L and 27 had TSH level <2.5 mIU/L. Low serum FT4 was in 9 (4.5%) subjects. The study revealed that, there was a significant positive correlation between positive TPO-Ab (>12 IU/mL) and serum TSH level of study subjects and there was negative correlation between serum TSH (>2.5 mIU/L) and serum FT4 in study subjects. Conclusion: TPO-Ab positivity in first trimester of pregnancy and TPOAb positivity was associated with higher TSH and low FT4 level. Bangladesh Journal of Medical Science Vol. 12 No. 02 April13 Page 164-170 DOI: http://dx.doi.org/10.3329/bjms.v12i2.14945